Metabolic Analyses and Evaluation of Antioxidant Activity in Purple Kohlrabi Sprouts after Exposed to UVB Radiation - Hyeon Ji Yeo; Soo-Yeon Lim; Chang Ha Park; Cha Young Kim; Ramaraj Sathasivam; Jae Kwang Kim; Sang Un Park (Antioxidants, 2022)
Various metabolites act as plant defense molecules due to their antioxidant abilities. This study aimed to investigate the influence of UVB irradiation on the accumulation of metabolites, including primary metabolites (sugar, sugar alcohols, amino acids, organic acids, and an amine) and secondary metabolites (anthocyanins, fatty acids, and phenolic acids), and its synergistic antioxidant ability, in purple kohlrabi sprouts. Metabolite analyses revealed a total of 92 metabolites in the sprouts. Specifically, the levels of most amino acids increased after 24 h of UVB treatment, and then slightly decreased in the kohlrabi sprouts. The levels of most sugars and sugar alcohols increased after 24 h of UVB treatment and then decreased. The levels of TCA cycle intermediates and phenolic acids gradually increased during the UVB treatment. Furthermore, the levels of some fatty acids gradually increased during the UVB treatment, and the levels of the other fatty acids increased after 6 h of UVB treatment and then decreased. In particular, the levels of most anthocyanins, known to be strong antioxidants, gradually increased after 24 h of UVB treatment. In the in vitro ABTS scavenging assay, UVB-treated purple kohlrabi sprouts showed increased scavenging ability. This may be attributed to the increased accumulation of metabolites acting as antioxidants, in response to UVB treatment. This study confirmed that UVB irradiation induced the alteration of primary and secondary metabolism in the kohlrabi sprouts.